PERAN KNOWLEDGE SHARING, LEARNING ORGANIZATION DAN KAPABILITAS INOVASI INDIVIDUAL TERHADAP KINERJA KARYAWAN - Satria Avianda Nurcahyo; Tri Wikaningrum (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2020)
The purpose of this study was to determine the effect of Knowledge Sharing, Learning Organization, and Individual Innovation Capability variables on the improvement of Employee Performance. The data used in this study were primary data in the form of questionnaires totaling 50 respondents of functional functional employees in the Center for Agricultural Technology Study in Central Java.The section consists of instructors, researchers, technicians and librarians. The sampling technique used in this study was purposive sampling. Testing of this study used path analysis and to test the effect of intervening variables used the sobel test. The results showed that (1) knowledge sharing has a positive effect on employee performance,(2) knowledge sharing has a positive effect on individual innovation capability,(3)individual innovation capability has a positive effect on employee performance,(4) learning organization has a positive effect on employee performance,(5) learning organization has a positive effect on individual innovation capability,(6) learning organization has a positive effect on knowledge sharing. In this study, of the 4 variables that have the most influence in relation to one another. Namely the Individual Innovation Capability variable with a beta amount of 0.530. This shows that the real employees in their hearts need support to explore themselves. Then get the freedom to express new innovations they find and be given training in new technologies. Digital technology and financial support are very important for the growth of innovation so that it can improve performance.Keywords: Knowledge Sharing, Learning Organization, Individual Innovation Capability, Employee Performance